Biological resource centers : knowledge hubs for the life sciences - Stern, Scott, 1969- (Brookings Institution Press, 2004)
Biological resource centres (BRCs) collect, certify and distribute organisms for use in research and in the development of commercial products. This text looks at the impact of BRCs through their role in facilitating cumulative knowledge in the life sciences and their roles as knowledge hubs.